Radiometric Cross-Calibration of an Aerial Sensor with Satellite Top-of-Atmosphere Reflectance - A. Nghien; M. Lei; M. Brédif; O. Hagolle (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Surface reflectance (SR) is essential for many remote sensing applications, but retrieving it from aerial images is challenging due to the lack of in-flight radiometric calibration and varying acquisition conditions. We propose a novel method for radiometric cross-calibration of aerial imagery using satellite Top-of-Atmosphere (TOA) reflectance. The method involves estimating at-sensor reflectance at the airborne altitude from satellite TOA reflectance, followed by spectral band adjustment and spatial alignment between satellite and airborne imagery. A linear radiometric model is derived to relate the Digital Number (DN) to the at-sensor reflectance from a selected subset of robust aerial-satellite pixel correspondences. The radiometric calibration parameter was retrieved using linear regression. The method is particularly suitable for airborne campaigns that lack onboard or in-situ radiometric calibration equipment. An ablation study is presented to analyze the selection of reliable reference pixels.